2018
DOI: 10.1007/s13592-018-0566-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional characterization of honey bee, Apis mellifera, hemocyte cell communities

Abstract: -Among invertebrates, cellular innate immunity is critical for wound healing and defense against parasites and pathogens. While the study of cellular immunity has received much attention in model insects, the study of hemocytes, including immune cells, in honey bees has received little attention. Much of our understanding of honey bee hemocytes is derived from a limited set of methodologies, predominately utilizing bright-field microscopy, which makes broad conclusions about honey bee cellular immunity difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 60 publications
1
22
0
10
Order By: Relevance
“…At the same time, queen bees show significant individual features of egg production during colonies feeding of pure sugar syrup and with the addition of biologically active substances. Insufficient amount of pollen in the bee colony probably reduces the effectiveness of the stimulating effect on the egg production of the queen bee by feeding them with sugar syrup and with the addition of biologically active substances [19,20].…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…At the same time, queen bees show significant individual features of egg production during colonies feeding of pure sugar syrup and with the addition of biologically active substances. Insufficient amount of pollen in the bee colony probably reduces the effectiveness of the stimulating effect on the egg production of the queen bee by feeding them with sugar syrup and with the addition of biologically active substances [19,20].…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…The humoral response involves secretion of antimicrobial peptides (AMP), and other effectors, melanization, and the enzymatic degradation of pathogens by different pathways [ 54 ]. Richardson et al [ 56 ] have identified and described the presence of two predominant cell types involved in the cellular response: granulocytes and plasmatocytes. Granulocytes exhibit a strong propensity for phagocytosis while plasmatocytes are involved in the encapsulation activity [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social behavior in the colony leads to nurturing behavior towards larvae, and in contrast, social immunity to control the spread of disease. Through the active removal of a sick brood, honey bees face the dangerous trade-off between the sacrifice of parasitized individuals and the growth of the colony as a whole: Hygienic behavior itself may also break down through Varroa -transmitted virus epidemics, placing limits upon its ability to control mite infestation [15,83]. Avoiding this breakdown is therefore critical to colony survival [15,83].…”
Section: Honey Bee Immunitymentioning
confidence: 99%